DNA vaccines elicit durable protective immunity against individual or simultaneous infections with Lassa and Ebola viruses in guinea pigs - Kathleen A. Cashman; Eric R. Wilkinson; Suzanne E. Wollen; Joshua D. Shamblin; Justine M. Zelko; Jeremy J. Bearss; Xiankun Zeng; Kate E. Broderick; Connie S. Schmaljohn (Taylor & Francis Group, 2017)
We previously developed optimized DNA vaccines against both Lassa fever and Ebola hemorrhagic fever viruses and demonstrated that they were protective individually in guinea pig and nonhuman primate models. In this study, we vaccinated groups of strain 13 guinea pigs two times, four weeks apart with 50 µg of each DNA vaccine or a mock vaccine at discrete sites by intradermal electroporation. Five weeks following the second vaccinations, guinea pigs were exposed to lethal doses of Lassa virus, Ebola virus, or a combination of both viruses simultaneously. None of the vaccinated guinea pigs, regardless of challenge virus and including the coinfected group, displayed weight loss, fever or other disease signs, and all survived to the study endpoint. All of the mock-vaccinated guinea pigs that were infected with Lassa virus, and all but one of the EBOV-infected mock-vaccinated guinea pigs succumbed. In order to determine if the dual-agent vaccination strategy could protect against both viruses if exposures were temporally separated, we held the surviving vaccinates in BSL-4 for approximately 120 days to perform a cross-challenge experiment in which guinea pigs originally infected with Lassa virus received a lethal dose of Ebola virus and those originally infected with Ebola virus were infected with a lethal dose of Lassa virus. All guinea pigs remained healthy and survived to the study endpoint. This study clearly demonstrates that DNA vaccines against Lassa and Ebola viruses can elicit protective immunity against both individual virus exposures as well as in a mixed-infection environment.